ASO Author Reflections: Improved Access, Improved Outcomes: Regional Increases of Curative-Intent Liver Therapies Are Associated with Improved Survival in Patients with CRCLM - Tsagkalidis, Vasileios; Ecker, Brett L. (Annals of surgical oncology, 2025)
There are no randomized data to confirm the survival benefit of these interventions compared with systemic therapy alone, with prior studies largely relying on patient-level observational data and subject to inherent limitations of selection bias and other unmeasured confounders.2, 3–4 Thus, the precise impact of liver-directed therapies on survival remains incompletely defined. The current study leveraged the observed variations in liver therapy rates across health service areas (HSAs) from 163 HSAs in the linked SEER-Medicare database to assess the precise impact of such changes on survival.5 This method allows each area to serve as its own control while adjusting for observed changes in the patient population over time. [...]modest increases in use of these interventions across a population can yield a measurable impact on regional CRCLM survival.